Density Functional Theory‐Based Calculations for 2D Hexagonal Lanthanide Metals. Issue 6 (10th April 2022) - Sangolkar, Akanksha Ashok; Jha, Sakshi; Pawar, Ravinder
Abstract: Scrutiny of the stability, properties, and applications of 2D metals belonging to s‐, p‐, and d‐block series has acquired intense research interest in the past few years. The present report is solely focused to systematically explore the stability and properties of 2D hexagonal (HX) lanthanides employing density functional theory calculations. To probe the dynamical stability of these materials, the phonon dispersion calculation is performed. The mechanical stability is analyzed on the basis of the 2D bulk modulus and elastic constant values. Further, to unravel the electronic properties of the 2D metals, electronic band structure, electron localization function, and the work function values are estimated. Moreover, en route to explore their magnetic properties, spin polarized density of states calculation is carried out and the ground state magnetic behavior is studied by considering ferromagnetic and antiferromagnetic spin configurations. Result explicitly demonstrates that 11 lanthanide metals are dynamically stable as an atomically thin 2D HX films. All of them are conducting in nature exhibiting ferromagnetic behavior in their ground state. These results offer the fundamentals of stability and properties of 2D HX lanthanides which can lay the foundation for exploring their diverse future applications. Abstract : In the present investigation, a systematic attempt is made to scrutinize the stability of 2D hexagonal (HX) lanthanides monolayer. Further, an attention is also devoted to unveil the electronic, thermal, and magnetic properties of the stable metal films. Interestingly, the atomically thin 2D lanthanide series elemental metals are found to be dynamically and mechanically stable.